Konsep Pendidikan Ibnu Khaldun dan Hubungannya dengan Perkembangan Pendidikan Islam di Pesantren Babussalam Teluk Bakung - Hayatun Sabariah; Ade Yuslina; Nur Ainun (Transformasi Manageria: Journal of Islamic Education Management, 2021)
Ibn Khaldun has the view that education must be taught gradually and understand the students. Education will be very useful if it is delivered gradually, gradually and a little by little. The teacher must also understand the readiness and thinking power of students to accept the lessons that are conveyed to him. Ibn Khaldun also taught that in educating to avoid harsh treatment of students. The position of the teacher as a guide for their students. Education must be managed with a good and well-planned system and be able to provide personal skills to students. Ibn Khaldun wanted a balanced curriculum between the teachings of the Qur'an as a concept and a source of knowledge. A teacher in Ibn Khaldun's view must master the components that show the quality of teaching that will make it easier for teachers to improve the quality of their teaching. With this viewpoint, if it is implemented properly in Islamic education, Islamic education will experience very good and significant developments. The results of the research that has been done, the researchers found that there is a correlation between the concept of Ibn Khaldun's education with the development of Islamic education. There is a positive and significant relationship in the concept of Ibnu Khaldun's education with the development of Islamic education at the Modern Babussalam Pesantren Teluk Bakung with a regression line Y = 19.96 + 0.66 X. There is a significant correlation between Ibnu Khaldun's concept of education and the development of Islamic education in Islamic boarding schools. Modern Babussalam Teluk Bakung, Tanjung Pura Subdistrict, after a regression test was carried out with the product moment formula with a calculation result of 0.816 with a strong or high level of relationship.